2005
DOI: 10.1021/ja0421497
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Addition of Nitrones to Activated Cyclopropanes

Abstract: In this paper, we demonstrate the first examples of chiral Lewis acid catalysis in the formation of tetrahydro-1,2-oxazines with very high enantioselectivity starting with diactivated cyclopropanes and nitrones (>90% yields and ee). Reactions with racemic substituted cyclopropanes provide approximately 1:1 diastereomeric tetrahydro-1,2-oxazine products with high enantioselectivity. Mechanistic information for the formation of the tetrahydro-1,2-oxazines is also detailed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(76 citation statements)
references
References 20 publications
(11 reference statements)
1
69
0
5
Order By: Relevance
“…Recently, Sibi et al developed a highly efficient asymmetric version of this reaction. [12] They reported that nitrones react with cyclopropane-1,1-dicarboxylates to afford tetrahydro-1,2-oxazine derivatives with high enantioselectivity in the presence of dbfox/Ni II (10 mol %; dbfox = 4,6-dibenzofurandiyl-2,2-bisoxazoline). When 2-substituted cyclopropane-1,1-dicarboxylates were used as substrates, and the quantity of the catalyst was increased to 30 mol %, the reactions proceeded smoothly to give the products with high ee values but with low diastereoselectivities (the cis/trans ratio ranged from 1.0:1.4 to 1.0:0.8).…”
mentioning
confidence: 99%
“…Recently, Sibi et al developed a highly efficient asymmetric version of this reaction. [12] They reported that nitrones react with cyclopropane-1,1-dicarboxylates to afford tetrahydro-1,2-oxazine derivatives with high enantioselectivity in the presence of dbfox/Ni II (10 mol %; dbfox = 4,6-dibenzofurandiyl-2,2-bisoxazoline). When 2-substituted cyclopropane-1,1-dicarboxylates were used as substrates, and the quantity of the catalyst was increased to 30 mol %, the reactions proceeded smoothly to give the products with high ee values but with low diastereoselectivities (the cis/trans ratio ranged from 1.0:1.4 to 1.0:0.8).…”
mentioning
confidence: 99%
“…Andere Wege zu 3,6-Dihydro-1,2-oxazinen Wenngleich es sich bei der Nitroso-HDA-Reaktion um eine hervorragende Synthesemethode für 3,6-Dihydro-1,2-oxazine handelt, sind auch alternative Wege zu diesen heterocyclischen Systemen bekannt, die bereits im Rahmen von Übersichten behandelt wurden. [86,87] Methoden zur Synthese monocyclischer 1,2-Oxazine umfassen die Ringschlussmetathese von Alkenen [88] und Eninen, [89,90] die Addition von Nitronen an Methoxyallene [91] und aktivierte Cyclopropane [92,93] sowie die Durchführung von Nitrosoaldolreaktionen. [94] Ein Beispiel für eine alternative Synthese bicyclischer 1,2-Oxazinsysteme ist die intramolekulare [3+2]-Cycloaddition von Nitronen (Schema 13).…”
Section: Nitrosocarbonyl-hda-reaktionen An Der Festen Phaseunclassified
“…Analogously, [68] treatment of malononitrile (76) Recently, Sibi [69] employed the Kanemasa 64/Ni(ClO 4 ) 2 · 3 H 2 O complex to obtain the first example of enantioselective addition of nitrones 80 to activated cyclopropanes 81, which undergo nucleophilic addition, resulting in the for- Scheme 33. mation of tetrahydro-1,2-oxazines 82 with very high enantioselectivities (Scheme 33). This chiral Lewis acid proved to be very effective, with the reactions proceeding in high yields at room temp.…”
Section: Perchlorate Salts As Lewis Acids In Enantioselective Synthesmentioning
confidence: 99%